We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
158
2
avatar+166 

A) Let \(f(x)\) be a polynomial of degree \(4\) with rational coefficients which has \(1+2\sqrt{3}\) and \(3-\sqrt{2}\) as roots, and such that \(f(0) = -154\) Find \(f(1)\)

 

B) Post your second question on a second post.

 May 6, 2019
edited by Melody  May 6, 2019
 #1
avatar+104882 
+1

The roots are  (1 + √12) ( 1-√12) (3 - √2)  and (3 + √2)

 

So........the polynomial is

 

a [ x - (1+√12) ] [ x - (1 - √12) ] [ x - ( 3 - √2) ] [ x- (3 + √2)]

 

Simplifying....we have that......

 

 

a [x^4 - 8 x^3 + 8 x^2 + 52 x - 77]  = 

 

And since f(0)  = -154

 

Then  -77a  = -154

So....a  = 2

 

So....the polynomial is

 

2x^4 - 16x^3 + 16x^2 + 104x - 154

 

And f(1)  =   2 - 16 + 16 + 104 - 154  =  -48

 

cool cool cool

 May 7, 2019
 #2
avatar+23318 
+1

A)

Let \(f(x)\) be a polynomial of degree \(4\)  with rational coefficients which has \(1+2\sqrt{3}\) and \(3-\sqrt{2}\)
as roots, and such that \(f(0) = -154\).
Find \(f(1)\)
.

 

Vieta:

\(\begin{array}{|rcll|} \hline \mathbf{f(x)} &=& \mathbf{ax^4+bx^3+cx^2+dx+e} \quad | \quad \text{polynomial of degree 4} \\\\ \dfrac{e}{a} &=& x_1x_2x_3x_4 \quad | \quad \text{Vieta-theorem},\ f(0) =e \\\\ \dfrac{f(0)}{a} &=& x_1x_2x_3x_4 \\\\ \mathbf{a} &=& \mathbf{\dfrac{f(0)}{x_1x_2x_3x_4}} \\\\ && \boxed{ f(0)=-154\\ x_1 = 1+2\sqrt{3}\\ x_2 = 1-2\sqrt{3}\\ x_3 = 3-\sqrt{2}\\ x_4 = 3+\sqrt{2} } \\\\ a &=& \dfrac{-154}{(1+2\sqrt{3})(1-2\sqrt{3})(3-\sqrt{2})(3+\sqrt{2})} \\\\ &=& \dfrac{-154}{(1-4\cdot 3)(9-2)} \\\\ &=& \dfrac{-154}{(-11)\cdot 7} \\\\ &=& \dfrac{ 154}{77} \\\\ \mathbf{a} &=& \mathbf{2} \\ \hline \end{array}\)

 

\(\mathbf{f(1)=\ ?}\)

\(\begin{array}{|rcll|} \hline \mathbf{f(x)} &=& \mathbf{ a(x-x_1)(x-x_2)(x-x_3)(x-x_4) } \\\\ f(1) &=& 2\left(1-(1+2\sqrt{3})\right) \left(1-(1-2\sqrt{3})\right) \left(1-(3-\sqrt{2})\right) \left(1-(3+\sqrt{2})\right) \\ &=& 2(2\sqrt{3}) (-2\sqrt{3}) (-2+\sqrt{2}) (-2-\sqrt{2})) \\ &=& 2(2\sqrt{3}) (-2\sqrt{3}) \left((-2)^2-2\right) \\ &=& 2(2\sqrt{3}) (-2\sqrt{3}) \cdot 2\\ &=& -16\cdot 3 \\ \mathbf{f(1)} &=& \mathbf{-48} \\ \hline \end{array}\)

 

laugh

 May 7, 2019

10 Online Users

avatar